Escapism in Sam Shepard’s The Buried Child - Irwan Sumarsono; Radina Anggun Nurisma; Imam Dui Agusalim; Eny Kusumawati; Elizabeth Anggraeni Amalo (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2021)
This study is a qualitative research that was conducted to analyze the escapism of Dodge’s in Sam Shepard’s The Buried Child. The writer uses the psychological approach to analyze the escapism of the main character, Dodge. Data were collected from some sources. The main source of the data was taken from the work entitled The Buried Child, while the supporting sources were derived from books, journals and from the internet. The collected data were analyzed using the descriptive analytic techniques. The study focused on the factors behind the reasons why Dodge withdraws himself from his real world, what makes him an escapist that makes the disintegration of his family. Dodge’s escapism takes place since he is betrayed by his wife and his own son who have an incestuous relationship that make them have a baby, and to cover this sin, the baby was buried. The betrayal of his wife and son makes him escapes from the reality into alcohol and makes him does not have any respect and love to his family